2006
DOI: 10.1177/205873920601900114
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Reactivity to rBET V1 and rPHL P1 in Patients with Oral Allergy Syndrome

Abstract: Oral Allergy Syndrome (OAS) in patients with pollen-induced rhinoconjunctivitis is caused by specific IgE recognizing cross-reacting epitopes of fruits and plants, which were clearly shown in vitro, but failed to be demonstrated in vivo by cross-challenges in the target organs. Considering the hypothesis of degradation of such epitopes in natural extracts, challenges with recombinant pollen allergens were done to evaluate the reactivity of the oral mucosa in OAS patients. Seventeen patients with OAS and rhinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Allergen‐challenge experiments performed in humans with recombinant allergens (e.g. rPhl p 1, rBet v 1) have confirmed that the sublingual mucosa is at least 10 times less reactive than the nasal mucosa or the skin (142). This is likely explained by the fact that only limited numbers of proinflammatory cells (such as mast cells) are present in the oral mucosa.…”
Section: Oral Mucosa and Immune Responsesmentioning
confidence: 99%
“…Allergen‐challenge experiments performed in humans with recombinant allergens (e.g. rPhl p 1, rBet v 1) have confirmed that the sublingual mucosa is at least 10 times less reactive than the nasal mucosa or the skin (142). This is likely explained by the fact that only limited numbers of proinflammatory cells (such as mast cells) are present in the oral mucosa.…”
Section: Oral Mucosa and Immune Responsesmentioning
confidence: 99%
“…However, it was evident that the sublingual mucosa could tolerate higher allergen levels than the mucosa in the nose or skin. 145 Clinically, use of the sublingual route is supported by numerous controlled trials showing its efficacy in asthma and rhinitis in adults and children. 143,146 Additionally, no severe adverse events occurred during the trial, and the most common adverse events were mild asthma attack and local rash.…”
Section: Oralmentioning
confidence: 99%
“…It has been suggested that the AD process of allergic inflammation is mediated by the T-helper type 2 (Th2) lymphocyte (2)(3)(4) Langerhans cells (LC) represent a subset of dendritic cells (DC) found in the stratified epithelia of skin and mucosae. LC expresses CD1a, but is distinguished from other DC by the presence of intracellular Birbeck granules.…”
Section: Introductionmentioning
confidence: 99%